Assignment of Contractual Position - Puente y Lavalle, Manuel De la (1978)
Based on the Comparative Law Congress held in London, the author develops the institution of the cession of the contract so that it is admitted in the positive legal regulations. To do this, first cover the legal nature, the characters and their effects of the aforementioned institution. Then depending on it, will go on to define the following: "picking up the main features that characterize the cession of contractual position that, as we have seen, are the following: a) be a contract concluded between three parties; b) its object is the assignment of the contractual position of one of the parties to another contract; e) have been this other contract with correlative benefits, whose reciprocal benefits have not been fully executed". Second, the author indicates that the assignment of contractual position is a legal act that can be practiced in relation to relations arising from all kinds of contracts with correlative benefits, provided that their reciprocal benefits have not been fully fulfilled, then it must be considered legislatively in the part relative to the General Theory of the Contract. For this reason, the author emphasizes highlighting the introduction in the Peruvian Civil Code of the institution of assignment of contractual position. This has already been accepted by modern doctrine and is also an unquestionable technical advance to facilitate the cession of the legal relationship that emanates from the contract. In this sense, the author highlights some details regarding the transferor and the transfer of the legal relationship. For this reason, it is recommended that the assignee give his consent in advance and this must not be considered perfected until he receives the information relating to the person of the transferee. On the other hand, the transferor must guarantee to the transferee the validity of the contract, but not the fulfillment thereof by the transferor. Likewise, the transferee and the transferee may reciprocally oppose the exceptions arising from the basic contract, especially the exception of non-compliance.